Self-* Pulse Synchronization for Autonomous TDMA MAC in VANETs - Mustafa, Mohamed (My University, 2012)
The problem of local clock synchronization is studied in the context of media access control(MAC) protocols, such as time division multiple access (TDMA), for dynamic and wireless ad hoc networks. In the context of TDMA, local pulse synchronization mechanisms let neighboring nodes align the timing of their packet transmissions, and by that avoid transmission interferes between consecutive timeslots. Existing implementations for Vehicular Ad-Hoc Networks (VANETs) assume the availability of common (external) sources of time, such as base-stations or geographical positioning systems (GPS). This work is the first to consider autonomic design criteria, which are imperative when no common time sources are available, or preferred not to be used, due to their cost and signal loss. We present self-* pulse synchronization strategies. Their implementing algorithms consider the effects of communication delays and transmission interferences. We demonstrate the algorithms via extensive simulations in different settings including node mobility. We also validate these simulations in the MicaZ platform, whose native clocks are driven by inexpensive crystal oscillators. The results imply that the studied algorithms can facilitate autonomous TDMA protocols for VANETs.
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Innovation och entreprenörskap (nyttiggörande); Transport; Computer and Information Science; Information & Communication Technology; Innovation & Entrepreneurship; Transport